2010
DOI: 10.1177/1947603510369552
|View full text |Cite
|
Sign up to set email alerts
|

In VitroCalcification of Immature Bovine Articular Cartilage

Abstract: Introduction:The zone of calcified cartilage (ZCC) anchors articular cartilage (AC) to subchondral bone through a layer of intermediate stiffness. The regulation and functional consequences of cartilage calcification may vary with depth from the articular surface. The hypothesis of this study was that the in vitro calcification of immature AC occurs selectively in the deep region and is associated with a local increase in stiffness.Methods:AC and growth plate cartilage (GPC) from calves were incubated in DMEM,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…To ensure cartilage formation at the other end of the tissue, we included TGF-β3 alongside insulin-transferrin-selenium, ascorbic acid, dexamethasone and β-glycerophosphate in an optimized osteochondral differentiation medium based on similar compositions reported in the literature [ 13 , 32 , 33 ]. We used β-glycerophosphate at a concentration of 2 mM, a level that can provide a source of phosphate without initiating osteogenesis or nonspecific mineral precipitation [ 34 ]. Indeed, we showed that this osteochondral medium could support either osteogenic or chondrogenic differentiation of hMSCs in agarose, depending on the presence or absence of BMP-2 in the culture medium ( Supplementary Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…To ensure cartilage formation at the other end of the tissue, we included TGF-β3 alongside insulin-transferrin-selenium, ascorbic acid, dexamethasone and β-glycerophosphate in an optimized osteochondral differentiation medium based on similar compositions reported in the literature [ 13 , 32 , 33 ]. We used β-glycerophosphate at a concentration of 2 mM, a level that can provide a source of phosphate without initiating osteogenesis or nonspecific mineral precipitation [ 34 ]. Indeed, we showed that this osteochondral medium could support either osteogenic or chondrogenic differentiation of hMSCs in agarose, depending on the presence or absence of BMP-2 in the culture medium ( Supplementary Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…A cell-mediated technique was proposed using β-glycerophosphate during deep zone chondrocyte cell culture (Hwang et al 2010). In this work, we have adapted a technique based on a double diffusion system (Boskey 1989; Hunter et al 1996) to control the calcification at an interface between a gel and a piece of bone.…”
Section: Discussionmentioning
confidence: 99%
“…We used these constructs for a 28 d course of osteochondral tissue engineering using a defined osteochondral differentiation medium that we have previously shown to be capable of supporting both osteogenesis and chondrogenesis (Figure 3A). [13] This medium included 2 × 10 −3 m β-glycerophosphate as a phosphate source, [32] transforming growth factor β3 (TGF-β3) to stimulate chondrogenesis, alongside supporting components such as insulin-transferrin-selenium, ascorbic acid, and dexamethasone.…”
Section: Gradient Materialsmentioning
confidence: 99%